Editorial Foreword to the Special Issue on Advances in Remote Sensing of Mountain Surface Processes - Li Peng; Wei Zhao; Gaofei Yin; Kai Yan; Tianjun Wu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Mountains play a crucial role in providing essential ecosystem services, including biodiversity conservation, regional climate regulation, and water resource preservation. Accurate and continuous monitoring of mountain surface processes is therefore vital for assessing environmental change and mitigating natural hazards. Remote sensing has emerged as a powerful tool for mountain research, yet the inherent complexity of these processes demands increasingly higher spatio-temporal resolution in observations. Against this backdrop, we launched the special issue “Advances in Remote Sensing of Mountain Surface Processes”. This initiative aims to systematically showcase cuttingedge research findings and innovative technologies from the global remote sensing community, specifically tailored to the complex terrain of mountainous environments. The special issue collects 13 articles and highlights a multidimensional exploration of mountain surface processes. The featured manuscripts cover a wide range of topics, spanning multi-source data fusion, methodological innovations, and diverse applications across various fields. This Editorial Foreword provides a comprehensive summary of theoretical advancements, methodological innovations, validation techniques, and practical applications of remote sensing in studying mountain surface processes. It also offers a thorough discussion of the challenges and future opportunities within this dynamic field.